The dynamics of population growth differential fertility and inequality: note. - Cy, Chu (American Economic Review, 1987)
This note challenges the proposition David Lam made in his attempt to examine the relationship between population growth and the distribution of income. In the first 2 sections of his paper in which no income mobility was allowed Lam successfully analyzed the effects of adding to the economy a group of immigrants (with income distribution different from the original residents) on 2 inequality measures. In the 3rd section Lam made the strong proposition that claims in effect in order to determine whether an increase in the ith-income groups fertility would increase or reduce the steady-state proportion of the ith-income group all the information needed is the ith row of the mobility matrix. A counterexample is presented here along with a correction for the error that is made in the derivation of Lams proposition.